2009
DOI: 10.1073/pnas.0911240107
|View full text |Cite
|
Sign up to set email alerts
|

Superatom spectroscopy and the electronic state correlation between elements and isoelectronic molecular counterparts

Abstract: Detailed in the present investigation are results pertaining to the photoelectron spectroscopy of negatively charged atomic ions and their isoelectronic molecular counterparts. Experiments utilizing the photoelectron imaging technique are performed on the negative ions of the group 10 noble metal block (i.e. Ni − , Pd − , and Pt − ) of the periodic table at a photon energy of 2.33 eV (532 nm). The accessible electronic transitions, term energies, and orbital angular momentum components of the bound electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 27 publications
4
95
0
1
Order By: Relevance
“…Employing the technique of velocity map imaging enabled us to quantify the electronically excited state characteristics of cluster element mimics, including their anisotropies which provide information on the symmetry of the orbitals from which the electrons are ejected. Extending these quantitative measurements to a variety of systems led us to similar findings of other promising element mimics [75,76].…”
Section: An Approach To Designing Nanoscale Catalystsmentioning
confidence: 69%
See 1 more Smart Citation
“…Employing the technique of velocity map imaging enabled us to quantify the electronically excited state characteristics of cluster element mimics, including their anisotropies which provide information on the symmetry of the orbitals from which the electrons are ejected. Extending these quantitative measurements to a variety of systems led us to similar findings of other promising element mimics [75,76].…”
Section: An Approach To Designing Nanoscale Catalystsmentioning
confidence: 69%
“…Although the spectra are not quantitatively identical, the similarities of the electronic excited states as well as the anisotropy parameters (b) are evident. Evidence that this is not a mere coincidence in the Pt/WC case is apparent by comparing spectra for other isovalent pairs such as TiO -, which reveals remarkable similarity [75] to that of Ni -, and similarly, ZrO -compares well with Pd -. Examples are shown in Figs.…”
Section: An Approach To Designing Nanoscale Catalystsmentioning
confidence: 89%
“…[14] Peppernick et al demonstrated that WC À ions exhibit isoelectronic correspondence with Pt À ions. [15] Because WC exhibits high thermal and electrochemical stability while resisting common catalyst poisons such as carbon monoxide and sulfur, [1][2][3] it has been identified as a suitable candidate to replace PGM catalysts in emerging renewable energy technologies, such as fuel cells and electrolyzers. [7][8][9][10][11][16][17][18] While there are many methods to synthesize WC nanoparticles (NPs), none of the current methods can simultaneously prevent sintering of the WC nanoparticles while also mitigating surface impurity deposition.…”
mentioning
confidence: 99%
“…Further Al 13 has a large electron affinity of 3.4 eV close to that of a Cl atom (9). These analogies have prompted the concept that selected stable clusters could mimic the electronic behavior of elemental atoms and be classified as superatoms forming a third dimension of the periodic table (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Because the properties of clusters change with size and composition, the superatoms offer the prospect of serving as the building blocks of nanomaterials with tunable characteristics (16,18).…”
mentioning
confidence: 99%